2022
DOI: 10.1038/s41598-022-09634-7
|View full text |Cite
|
Sign up to set email alerts
|

Micro-replication platform for studying the structural effect of seed surfaces on wetting properties

Abstract: Biological surfaces in plants are critical for controlling essential functions such as wettability, adhesion, and light management, which are linked to their adaptation, survival, and reproduction. Biomimetically patterned surfaces replicating the microstructures of plant surfaces have become an emerging tool for understanding plant–environment interactions. In this study, we developed a two-step micro-replication platform to mimic the microstructure of seed surfaces and demonstrated that this initial platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…These samples were prepared to investigate systematically how the combined influence of surface geometry and wettability impacts both the evaporation dynamics and resulting patterns formed by deposited particles. [32,[41][42][43][44] Figure 1C portrays the fabricated microstructured surfaces, featuring micropillars with a diameter (d) and pitch (p) of 4.5 and 40 μm, respectively, as well as the microcavities with a wall thickness (t) and hexagonal side length (l) of 3 and 40 μm, respectively. To investigate the wetting and evaporation dynamics of these samples in the context of sensing applications, a test system was designed using liquid droplets blended with nanoparticles, simulating the analyte-laden colloidal suspension.…”
Section: Wetting Properties and Evaporation Dynamicsmentioning
confidence: 99%
“…These samples were prepared to investigate systematically how the combined influence of surface geometry and wettability impacts both the evaporation dynamics and resulting patterns formed by deposited particles. [32,[41][42][43][44] Figure 1C portrays the fabricated microstructured surfaces, featuring micropillars with a diameter (d) and pitch (p) of 4.5 and 40 μm, respectively, as well as the microcavities with a wall thickness (t) and hexagonal side length (l) of 3 and 40 μm, respectively. To investigate the wetting and evaporation dynamics of these samples in the context of sensing applications, a test system was designed using liquid droplets blended with nanoparticles, simulating the analyte-laden colloidal suspension.…”
Section: Wetting Properties and Evaporation Dynamicsmentioning
confidence: 99%
“…These structures are crafted using methods such as lithography [7], sol-gel [8], selfassembly [9,10], direct replication using Anodic Aluminum Oxide (AAO) [11][12][13][14], and SPPW [15][16][17]. Nanoimprint lithography (NIL) [18][19][20][21][22], a technology employing roll imprinting to create nanopatterns by coating a resin that cures with ultraviolet light, is particularly esteemed for its simplicity and cost-effectiveness. However, the nature of NIL, involving the transfer of thin layered materials through pressure to create patterns on a new surface, imposes limitations on achieving structures with high aspect ratios.…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] We focused on the main water-repellent surface production methods: coating with low-surfaceenergy materials [27][28][29][30][31] and generating nano/microstructures via lithography and template replication. [32][33][34][35][36][37][38] However, surface coatings are limited by their lack of durability, often requiring frequent reapplication to maintain effectiveness. [39][40][41] Previous studies on longterm water-resistance stability have revealed a significant reduction in contact angles over time.…”
Section: Introductionmentioning
confidence: 99%